“Some are healthy and others not”: Characterization of vended food products by Accra-based food retailers - Nanema, Silver; Adjei, Akosua; Amevinya, Gideon Senyo; Laar, Amos (Frontiers in Public Health, 2022)
Background and objectives: Increasing the availability of healthy foods within food retail outlets can improve consumers’ food environments. Such actions or inactions by food retailers may affect people’s food purchasing and consumption behaviour. This study explored Accra-based food retailers’ perceptions and appreciation of ‘healthiness of food as a concept. It also documented, measures that food retailers adopt to encourage healthy food choices. Methods: In-person semi-structured interviews were conducted with owners and managers of Accra-based supermarkets (n=7) and corner stores (n=13) in March 2021. The interviews were recorded, transcribed, coded and analysed thematically. Results: The retailers’ understanding of healthy food or lack thereof, is exemplified by such expressions as “health, absence of disease, longevity, balanced diet, diversity, sanitation, and certification”. A handful of retailers described what they sell as products that meet consumer needs, harmless, or generally good. Very few retailers described the food they sell as “junk”, high in sugar, fat, and salt, or energy-dense but nutrient-poor foods, or as food that could pose some health risk to consumers. However, some retailers indicated that they advise their customers against the overconsumption of some foods. Conclusion: Overall, Accra-based retailers have a fair understanding of what constitutes healthy food – exhibiting limited knowledge of the connection between very salty, very sugary, and very fatty foods and health outcomes. Retailers in Accra require interventions that improve their food, health, and nutrition literacy. Improving retailers’ food and nutrition literacy may improve the availability of healthier options in food retail outlets in Accra.